PENGARUH KEPERCAYAAN DAN KEAMANAN TERHADAP NIAT PEMBELIAN PRODUK FASHION SECARA ONLINE - Nabiil Hilmi Makaarim; Rini Kuswati (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2024)
This study aims to analyze the effect of trust and security on the purchase intention of fashion products online. The research method used in this research is quantitative method. The sampling technique in this study is nonprobability sampling technique with purposive sampling method, data obtained from primary data distributed through closed questionnaires using a Likret scale. The population in this study were consumers who had shopped for fashion online, totaling 182 respondents. The PLS-SEM Analysis technique is used as a tool to predict and explore complex models with less stringent requirements on the data. The data analysis technique in this study uses Partial Least Square (PLS) using the help of SMARTPLS Software. The results of this study indicate that trust is able to mediate the relationship between security and online fashion purchase intentions.